Long-Term Survival in Metastasized Leiomyosarcoma: A Case Report and Review of the Literature. Issue 5 (September 2015) - Schönknecht, Christine; Hadjamu, Miriam; Oechsner, Markus; Andratschke, Nicolaus; Duma, Marciana-Nona
Background: Leiomyosarcoma of the mesosigma is a very rare entity, with low 5-year survival rates. Treatment consists of resection of the primary tumor and, if applicable, of synchronous or metachronous metastases. Local treatment options for metastatic disease should be exploited as long as possible, as response to chemotherapy is reportedly disappointing. Stereotactic radiotherapy is a fairly new locally effective treatment option which has been well established in stereotactic radiotherapy of lung tumors. Whether repeated stereotactic radiotherapy sessions for treatment of lung metastases can be safely and successfully performed over a long time period is not yet well documented. Case report: We present the case of a 71-year-old female patient who had a primary diagnosis of lung metastases 12 years ago. Atypical resections of 4 lung metastases were performed in 2001 and 2002. Between 2004 and 2011, 7 sessions of stereotactic body irradiation of lung metastases were performed. All stereotactic treatment were tolerated well (no radiation pneumonitis, FEV1 was 1.3 L [67.8%] in 2004 and 0.99 L [56.3%] in 2011). Conclusions: The present case could demonstrate that a repetitive treatment of lung metastases with multiple stereotactic radiotherapy sessions can lead to long-term survival with a good quality of life.